Technology-based Business Idea Blueprint Report IZ-LAMIC Enterprise Digital Prayer Mat / Fatin Nadzirah Izzatie Azman - Azman, Fatin Nadzirah Izzatie (2020)
IZ-lamic Enterprise offers a product that have being generated with the technological advances. Our team will ensure that we would meet the satisfaction from our customer by serving them a good services and introducing them our high quality product. IZ-lamic Enterprise is located in Rawang, Selangor. The form of our business is a partnership owned by Chief Executive Officer (CEO) and one of her team management. Both partners will be taking hands-on management roles in the company. In addition, we have assembled a board of advisors to provide management expertise.